Association of disease severity and genetic variation during primary Respiratory Syncytial Virus infections - William Bender; Yun Zhang; Anthony Corbett; Chinyi Chu; Alexander Grier; Lu Wang; Xing Qiu; Matthew N. McCall; David J. Topham; Edward E. Walsh; Thomas J. Mariani; Richard Scheuermann; et al. (BMC, 2024)
Abstract Background Respiratory Syncytial Virus (RSV) disease in young children ranges from mild cold symptoms to severe symptoms that require hospitalization and sometimes result in death. Studies have shown a statistical association between RSV subtype or phylogenic lineage and RSV disease severity, although these results have been inconsistent. Associations between variation within RSV gene coding regions or residues and RSV disease severity has been largely unexplored. Methods Nasal swabs from children (< 8 months-old) infected with RSV in Rochester, NY between 1977-1998 clinically presenting with either mild or severe disease during their first cold-season were used. Whole-genome RSV sequences were obtained using overlapping PCR and next-generation sequencing. Both whole-genome phylogenetic and non-phylogenetic statistical approaches were performed to associate RSV genotype with disease severity. Results The RSVB subtype was statistically associated with disease severity. A significant association between phylogenetic clustering of mild/severe traits and disease severity was also found. GA1 clade sequences were associated with severe disease while GB1 was significantly associated with mild disease. Both G and M2-2 gene variation was significantly associated with disease severity. We identified 16 residues in the G gene and 3 in the M2-2 RSV gene associated with disease severity. Conclusion These results suggest that phylogenetic lineage and the genetic variability in G or M2-2 genes of RSV may contribute to disease severity in young children undergoing their first infection.